An Enjoyable Application to Learn English for SMK Yapim Biru-Biru - Gurusinga, Mona Fitri; Bukit, Herawati; manullang, frengki; Simanjuntak, Aprilius; simanjuntak, Afrilius (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
A number of things can impact the process of learning outcomes. It might be aptitude, passion, learning concepts, learning motivation, and so on. The ability of a speaker or teacher to impart knowledge, create an engaging learning environment, and increase students' motivation to learn—especially English—is equally crucial. Students frequently experience boredom when learning English and struggle to comprehend what they are learning. Despite the fact that learning English is crucial because it is now a necessity in daily living, including family life. As previously mentioned, the goal of this magazine is to find ways to make learning engaging so that students comprehend the methods and the English instruction provided by lecturers. And how do instructors perceive students' comprehension of learning English? Are there any further factors in engaging in enjoyable English language study. The application is completed for SMK Yapim Biru-Biru. Based on the lecturer's experience teaching and observation of the students' English-learning conditions, there are learning outcomes and strategies that appear to be liked by the students themselves from this point on.